Checklist on Establishing Post-2020 Emission Pathways - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
This “checklist” is designed to support countries in the development and presentation of medium- and long-term emission pathways. The development of these pathways is crucial to allow countries to plan their international commitments in a manner consistent with future economic development, and to construct a suitable package of policies and measures that build synergies between the two, in many cases including the use of carbon pricing instruments. This work is expected to be of particular use to countries devising their intended nationally determined contributions (INDCs) to submit to the United Nations Framework Convention on Climate Change (UNFCCC).